Non-Formal Education : Myth or Panacea for Pakistan - Khawaja, Sarfraz and Brennan, Barrie (Islamabad Mr. Books, 1990)
A guidebook for Educational Planners as an entry point to prepare the nation for the 21st Century.
Include Figures, Tables, Bibliography and Index.
Keywords: Non-formal education -- Pakistan -- Adult education